Pengaruh Corporate Governance, Ukuran Perusahaan, Profitabilitas, dan Leverage Terhadap Pengungkapan Sustainability Report (Studi Empiris Perusahaan Pertambangan dan Industri Dasar & Kimia Yang Terdaftar Di Bursa Efek Indonesia pada Tahun 2021-2022) - Rahmannita, Nur (BISMA : Business and Management Journal, 2024)
A sustainability report is a report that provides information about the impact of a company on environmental and social aspects apart from economic aspects. With this report regarding the disclosure of sustainability reports, it is hoped that it will attract the attention of companies in global business and increase the trust of the public and stakeholders to invest their capital in the company. This research aims to analyze the influence of corporate governance, company size, profitability and leverage on sustainability report disclosure. The population in this research is 143 companies listed on the Indonesia Stock Exchange (BEI) in 2021-2022. This research sample was selected using purposive sampling. The number of samples in this research is 45 sample companies in the 2021-2022 period. The analysis tool uses multiple linear regression tests. The results of this research show that managerial ownership has no effect on sustainability report disclosures, independent commissioners have an effect on sustainability report disclosures, company size has no effect on sustainability report disclosures. Meanwhile, profitability has an effect on sustainability report disclosure and leverage has no effect on sustainability report disclosure.